A HISTORICAL SURVEY OF AMALGAMATION OF THE NORTHERN AND SOUTHERN POLICE DEPARTMENTS OF NIGERIA IN 1930 - Daniels, Famoye Abiodun (European Scientific Journal, ESJ, 2012)
This paper examines the historical dynamics that metamorphosed into the amalgamation of the Northern and Southern Police Departments of Nigeria by the British colonial government in 1930. The paper posits that the reform was largely part of the British extant colonial policy directed at the exploitation of Nigeria. The paper argues further that the amalgamation was desired more as a means of alleviating British economic difficulties of the 1920s and the 1930s. The paper therefore concludes that, contrary to the colonial government’s claim that the amalgamation was strictly designed for the development of Nigeria; the amalgamation was actually projected towards the maximisation of British colonial interest at the expense of Nigeria.